2019
DOI: 10.5897/jpbcs2018.0788
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among regenerated tall coconut (Cocos nucifera L.) accessions from multivariate analyses using reliable short list of morphological descriptors in Cte dIvoire.

Abstract: Genetic relationships among 18 regenerated tall coconut accessions from International Coconut Genebank for Africa and Indian Ocean (ICG-AIO) located at Côte d'Ivoire were studied. Analyses were achieved from 17 quantitative characters of the reliable minimal list of agro-morphological descriptors for coconut proposed by Coconut Genetic Resources Network (COGENT) in 2007. From achieved Multivariate Analyses (MVA) two geographical clusters including Afro-Indian and Far East were observed in the first generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
2
0
2
Order By: Relevance
“…They consist in the group of Afro-Indian populations (WAT, WAT6 and LCT) and the group of Latin America and South Pacific populations (PNT01, PNT02, SIT and GPT). The classification corroborates morphological clustering of Tall coconut accessions From International Coconut Genebank for Africa and Indian Ocean (ICG-AIO) as reported by Konan (2008) and Yao et al (2019). Thus, the present study revealed that from two genetic pools into ICG-AO they are the coconut accessions accounting the best male parental individuals and the ones with good seed production abilities under artificial regeneration.…”
Section: Discussionsupporting
confidence: 90%
“…They consist in the group of Afro-Indian populations (WAT, WAT6 and LCT) and the group of Latin America and South Pacific populations (PNT01, PNT02, SIT and GPT). The classification corroborates morphological clustering of Tall coconut accessions From International Coconut Genebank for Africa and Indian Ocean (ICG-AIO) as reported by Konan (2008) and Yao et al (2019). Thus, the present study revealed that from two genetic pools into ICG-AO they are the coconut accessions accounting the best male parental individuals and the ones with good seed production abilities under artificial regeneration.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, WAT is considered as control in all experimental plots of Tall coconut palms at the Marc Delorme station. For each character, weighted means were done following relation [18]:…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The YSI character is estimated by measuring the height of 11 leaf scars, and it is used to predict the increase in yearly stem height of the coconut palms over specific years (Martial et al 2019). The productive period of the coconut palms is associated with the YSI character since the higher the coconut stem height, the more challenging to harvest the nuts.…”
Section: Introductionmentioning
confidence: 99%